THE ESSENCE AND CONTENT OF THE PROCESS OF EDUCATION - Botirova Mukarram (Galaxy International Interdisciplinary Research Journal, 2022)
Peculiarities of the upbringing process The upbringing process is the process of personality formation and development, which includes both purposeful external influence and self-education of the individual